Redistribution Policy and Inequality Reduction in OECD Countries What Has Changed in Two Decades? - Immervoll, Herwig (OECD Publishing, 2011)
We use a range of data sources to assess if, and to what extent, government redistribution policies have slowed or accelerated the trend towards greater income disparities in the past 20-25 years. In most countries, inequality among "non-elderly" households has widened during most phases of the economic cycle and any episodes of narrowing income differentials have usually not lasted long enough to close the gap between high and low incomes that had opened up previously. With progressive redistribution systems in place, greater inequality automatically leads to more redistribution, even if no policy action is taken. We find that, in the context of rising market-income inequality, tax-benefit systems have indeed become more redistributive since the 1980s but that this did not stop income inequality from rising: market-income inequality grew by twice as much as redistribution. The redistributive strength of tax-benefit systems weakened in many countries particularly in the most recent decade. While growing market-income disparities were the main driver of inequality trends between the mid-1980s and mid-1990s, reduced redistribution was often the main driver in the ten years that followed. Benefits had a much stronger impact on inequality than social contributions or taxes, despite the much bigger aggregate size of direct taxes. As a result, redistribution policies were often less successful at counteracting growing income gaps at the bottom in the top half of the income distribution
Keywords: Employment; Social Issues/Migration/Health